Table of Content - - (Journal of Arabic Language Sciences and Literature, 2025)
Table of Content: 1. The art of analogy in the poetry of Aws bin Hajarh Dr. Said Obaid Abdullah Al-Wahaibi 2. Analysis of Arabic Phonetic Articulation Point Ms. Salma Mohammed Al-Mutairi 3. Mechanisms of Artistic Imagery in the Poetry Collection Sacrifices of Farewell by Abdullah Bashrahil Co-Prof. Sultan Saeed Abu Dabeel 4. The speaker and communicative aids in the Maqamat of Badi al-Zaman al-Hamdhani - The Kufi Maqamat as an example Ms. Alia Ali Saeed Alketbi ,Dr. Muhammad Hilmi bin Abdullah bin Jaafar 5. The sociological aspect of language according in Blaggat Alnisa to Aben Taiffor (280h): The discourse of woman with her husband Ms. Alhanouf Ali Al-Feredi, Prof. Abdul-Lateef Marzouq Al-Solami 6. Israelite stories between language and myth Co-Prof. Nada Abdullah Aldaher 7. A structural semiotic approach to the Quranic character of Yunus, peace be upon him, and the aesthetics of place in the Quranic story Mr. Mahmoud Jamal Rayyan